Negative correlation between ACE2 gene expression levels and loss of taste in a cohort of COVID-19 hospitalized patients: New clues to long-term cognitive disorders - Braga-Paz, Isabela; Ferreira de Araújo, João Locke; Alves, Hugo José; de Ávila, Renata Eliane; Resende, Gustavo Gomes; Teixeira, Mauro Martins; de Aguiar, Renato Santana; de Souza, Renan Pedra; Bahia, Diana (Frontiers in Cellular and Infection Microbiology, 2022)
While coronavirus disease 2019 (COVID-19) symptoms are acute, and most patients fully recover, many patients experience long-term health consequences in what has become known as long-COVID syndrome. which is present in about 30% of patients, even those who developed only mild acute COVID symptoms. Initially, one of the most prevalent symptoms of SARS-CoV-2 infection was the loss of smell (anosmia), found in 60-70% of all cases. Anosmia used to occur early, concomitantly with other symptoms, and often persisted after recovery for an extended period, sometimes for months. In addition to smell disturbance, COVID-19 has also been associated with loss of taste (ageusia). The prevalence of anosmia and ageusia has decreased since late 2020, coinciding with the emergence of SARS-CoV-2 variants of concern. The latest research suggests that SARS-CoV-2 could spread from the respiratory system to the brain through receptors in sustentacular cells localized to the olfactory epithelium. The virus invades human cells via the obligatory receptor, angiotensin-converting enzyme II (ACE2), and a priming protease, TMPRSS2, facilitating viral penetration. ACE2 and TMPRSS2 are expressed in sustentacular cells. We evaluated 102 COVID-19 hospitalized patients, of which 17.60% presented anosmia and 9.80% ageusia. ACE1, ACE2, and TMPRSS2 gene expression levels in nasopharyngeal tissue were obtained. Logistic regression models were generated to estimate individual effects of variables on ageusia and anosmia. Association of ACE2 expression levels with ageusia was observed (OR: 1.35; 95% CI: 1.098-1.775).. We hypothesize that there is an association between early anosmia and-or ageusia and long-lasting neurological disorders following SARS-CoV-2 infection.